Spatiotemporally resolved emissions and concentrations of styrene, benzene, toluene, ethylbenzene, and xylenes (SBTEX) in the US Gulf region - C.-T. Wang; B. H. Baek; W. Vizuete; L. S. Engel; J. Xing; J. Green; M. Serre; R. Strott; J. Bowden; J.-H. Woo (Earth System Science Data, 2023)
Styrene, benzene, toluene, ethylbenzene, and xylenes (SBTEX) are established neurotoxicants. SBTEX contains hazardous air pollutants (HAPs) that are released from the petrochemical industry, combustion process, transport emission, and solvent usage sources. Although several SBTEX toxic assessment studies have been conducted, they have mainly relied on ambient measurements to estimate exposure and limit their scope to specific locations and observational periods. To overcome these spatiotemporal limitations, an air quality modeling system over the US Gulf region was created, predicting the spatially and temporally enhanced SBTEX modeling concentrations from May to September 2012. Due to the incompleteness of SBTEX in the official US Environmental Protection Agency (EPA) National Emission Inventory (NEI), the Hazardous Air Pollutions Imputation (HAPI) program was used to identify and estimate the missing HAP emissions. The improved emission data were processed to generate the chemically speciated hourly gridded emission inputs for the Comprehensive Air Quality Model with Extensions (CAMx) chemical transport model to simulate the SBTEX concentrations over the Gulf modeling region. SBTEX pollutants were modeled using the Reactive Tracer feature in CAMx that accounts for their chemical and physical processes in the atmosphere. The data show that the major SBTEX emissions in this region are contributed by mobile emissions (45 %), wildfire (30 %), and industry (26 %). Most SBTEX emissions are emitted during daytime hours (local time 14:00–17:00), and the emission rate in the model domain is about 20–40 t h−1, which is about 4 times higher than that in the nighttime (local time 24:00–04:00, about 4–10 t h−1). High concentrations of SBTEX (above 1 ppb) occurred near the cities close to the I-10 interstate highway (Houston, Beaumont, Lake Charles, Lafayette, Baton Rouge, New Orleans, and Mobile) and other metropolitan cities (Shreveport and Dallas). High styrene concentrations were co-located with industrial sources, which contribute the most to the styrene emissions. The HAPI program successfully estimated missing emissions of styrene from the chemical industry. The change increased total styrene emissions by 22 %, resulting in maximum ambient concentrations increasing from 0.035 to 1.75 ppb across the model domain. The predicted SBTEX concentrations with imputed emissions present good agreement with observational data, with a correlation coefficient (R) of 0.75 (0.46 to 0.77 for individual SBTEX species) and a normalized mean bias (NMB) of −5.6 % (−24.9 % to 32.1 % for the individual SBTEX species), suggesting their value for supporting any SBTEX-related human health studies in the Gulf region. The SBTEX data were published at Zenodo (https://doi.org/10.5281/zenodo.7967541) (Wang et al., 2023), and the HAPI tool was also published at Zenodo (https://doi.org/10.5281/zenodo.7987106) (Wang and Baek, 2023).